Perancangan Sistem Administrasi Perpustakaan Berbasis Web Pada SMP Negeri 5 Kota Jambi - Muhammad Ihsan; Abdul Haris; Beni Irawani (JOURNAL VISION TECHNOLOGY (V-TECH) ISSN : 2622-9315 (Online - Elektronik), 2021)
The library is one of the work units in the form of a place to organize, manage, store and collect library material collections systematically to be used by users as information as well as a fun learning tool. With the development of technology makes people think to be able to work more effectively and efficiently. One of them is to make the manual system into a computerized system. The administrative system that runs the SMP Negeri 5 Jambi City library in processing data such as book data, borrowing and returning is still done by recording manually, making it difficult for officers to find information on book data, borrowing and returning books. In this study, a web-based administration system was designed using the waterfall method and Microsoft visual studio code software, XAMPP and several other supporting software. With this research, it produces a library administration system that can facilitate book lending and manage member data, admin data, book data, borrowing data, return data, fines, and print loan reports, member data reports and book data reports. Which is at SMP Negeri 5 Jambi City.